History of the Russian Legal Regulation Detection, Correction of Judicial Criminal Procedural Errors in the Period Until 1864 - S. H. Savchenko (Сибирское юридическое обозрение)
This paper examines the history of criminal identification and correction of errors. The Novgorod court charter in 1456, Sudebnik 1497 and 1550., Catholic Code of 1649, Quick image processes or litigation in 1715, the Decree "On the shape of the court" in 1723 are analyzed.